'A wholly racialized world': racial inequalities and peer review in leisure and tourism studies. Issue 5 (3rd September 2022) - Bandyopadhyay, Ranjan
ABSTRACT: This paper is a critical autoethnographic exploration of the racial inequalities in leisure and tourism studies by taking the case of the peer review process and the place of scholars of colour within it. Precisely, I challenge the White logic in the peer review process in leisure and tourism studies. While furthering recent scholars' efforts in attempting to challenge positivist epistemologies on mainstream leisure and tourism studies, I ask pertinent questions. Why does academia have to still allow/accept Euro-Amero-centric dogmas to dictate the peer review process? When will academia's enthralment with the 'White supremacy' (i.e. preaching the Others about scientific orthodoxy) come to an end, if at all? I explore how despite all the glorifying talks of diversity, inclusiveness, end of inequality, and sustainable development in academia, 'we still live in a wholly racialized world' where 'privileged whites are supposed to [and in reality] protect and perpetuate not only white myths but also raciology itself'. What if I were a White scholar? Would the reviewers then have made similar comments? This paper is an attempt to resist the hegemonic White logic so that the scholars of colour can theorise about their academic lives with dignity.